SIKAP NASABAH BANK KONVENSIONAL TERHADAP PERBANKAN SYARIAH PASCA FATWA MUI (Studi Kasus pada Mahasiswa Fakultas Ekonomi Universitas Jenderal Soedirman Purwokerto) - Umi Widyastuti; Nurhayati Indiyastuti; Utami Puji Lestari (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2007)
Conventional banking in Indonesia have been surprised with “fatwa Majelis Ulama Indonesia” (MUI) about excessive interest. Some people who reject it would beworry about rush in conventional bank. The purpose of this research is to know the attitude of conventional bank’s customer toward syariah-banking, especially PT BankMuamalat Indonesia Purwokerto. Fishbein’s model is used to analysize the attitude of conventional bank’s customer toward syariah banking. Then using interval scale, its score would be categorized in five interval namely very positive, positive, neutral, negative and very negative. It shown that the people who has account in conventional bank, have neutral attitude toward syariah-banking pasca “fatwa MUI”.